Effect of phenolic compounds Extractions of Green tea (Camellia sinesis 1) On the glutathione -S- Transferase Alloxan Experimental Induced-Diabetic Rabbit. - Abdulhameed, Buthayna (Tikrit Journal of Pharmaceutical Sciences, 2010)
Dinbeen Mellitus is considered as a member of oxidative stress syndroms. It is associated with an imbalance between types of roo radicals nd scavenger’ system. “This study showed the effect of the polyphenol compounds extracted from green tea (Camellia Sinesis L.) on alloxan induced diabetic rabbits to determine hei role in treatment of diabetes mellicis, their effect on enzymatic anticxidant and to know the histological effects on the diabetic kidney. The rabbits grou was divided into four groups, each group cossist of 7 rabbits. The first group was healthy rabbits (poral 2roup) as compared With secnd group The second group disbetic without treatment as control group wih the last three groups. The third group diabetic treated wit exmuct of green tea 100mp/k of body weight as single daily dose. The fourth grou diabetic treated wih extract of green tea 200mp/Ke of body weigh ws a single daily dose. After treatrent for twenty week blood and tissue sumples were taken for analysis and the result were as follow : There was signifisan desicase in GSTS When polyphenal extract of green tea was used wilh dose rate 100mg (kg of body weight (fourth group) gave u significant increase (n<D.05 ) in all paruncters es ‘compared with, diabetic grou (without treatment ), The present results revealed thi alloan wos effectively induced disbetes by partial destruction of bells of pussies ‘which lead lo elevation of blood glense level. As consequence of hyperglycemia the abnormal effet was obvions in certain tissues in the body which wiributed to (he effect of diabetes Histological investigations shows that all he lesions in the kidney that result fiom diabetes such a hypertrophy. degensration ond hylanosis of hc glomeruli.